Warm nights increase Fusarium Head Blight negative impact on barley and wheat grains - Martínez, Mauro; Biganzoli, Fernando; Arata, Agustin Francisco; Dinolfo, María Inés; Rojas, Dante Emanuel; Cristos, Diego Sebastian; Stenglein, Sebastián (Elsevier, 2022)
The disease known as Fusarium Head Blight (FHB) is one of the most devastating cereal diseases, among which Fusarium graminearum and Fusarium poae have been isolated to be the main etiological agents in cereal crops such as barley and wheat. Currently, global climate change is one of the major concerns worldwide, and temperature is likely to be one of the most affected variables in the future. However, it is unknown how these changes will affect fungal diseases such as FHB. The present research aimed to study the F. graminearum/F. poae-barley/wheat pathosystem under future climatic conditions. The effects of the increase in night temperatures (3 °C) on disease variables, grain quality, and mycotoxin contamination were evaluated under field conditions over three years (2016, 2017, and 2018). For both crops, the results showed that warm nights favoured F. graminearum development over F. poae, reducing grain quality parameters and increasing the mycotoxin concentration significantly. The results obtained along the present work provide a better understanding of the F. graminearum/F. poae-barley/wheat pathosystem and the basis for potential future research related to climate change studies under field conditions directly impacting food quality and safety.